Types of Policies for the Joint Diffusion of Electric Vehicles with Renewable Energies and Their Use Worldwide - Cristina Sousa; Evaldo Costa (Energies, 2022)
A large reduction in greenhouse gas (GHG) emissions will be needed in the coming decades to keep global warming well below 2 °C. Together, energy and transport sectors are responsible for around ¾ of carbon dioxide (CO2) emissions worldwide. The transition to a low-carbon economy involves an increase in the share of renewable energies in power grid and the electrification of the transports thus demanding policies focused on the joint diffusion of the two technologies This study adopted a hybrid methodology to examine several types of policies and their implications in the use and diffusion of the electric vehicles charged with renewables. We argue that it is not enough to have policies to expand electric mobility with renewable sources. The results reveal that production and technology represent ⅓ of electric vehicles and renewables policies. Broad coverage of policies does not translate into market gains since 20% of the countries that encourage electric vehicles have a low market share. Policies need to be broad, consistent, reach more countries and promote synergies between renewables and electric mobility to provide the conjoint diffusion of both technologies and allow the CO2 emission mitigation targets for 2030 to be achieved. This study contributes to research on sustainable policies and innovations to decarbonizing the energy and transport sectors.